Oncoplastic partial breast reconstruction improves patient satisfaction and aesthetic outcome for central breast tumours. Issue 5 (20th March 2019) - Shechter, Shirley; Friedman, Or; Inbal, Amir; Arad, Ehud; Menes, Tehillah; Barsuk, Daphna; Gur, Eyal; Barnea, Yoav
Abstract : Background: Patients with centrally located tumours involving the nipple–areolar complex (NAC) who undergo breast‐conserving treatment (BCT) are at high risk for breast deformity and asymmetry. Immediate oncoplastic breast reconstruction (OBR) can have a favourable impact on surgical outcome. Methods: We retrospectively compared aesthetic outcomes and patient satisfaction among women treated with NAC lumpectomy and immediate OBR with patients treated with BCT alone. Aesthetic outcome was evaluated by independent observers, and patient satisfaction was assessed by the BREAST‐Q questionnaire. Results: A total of 24 patients were studied, 12 in each group. Demographics and oncological staging were similar in both groups, apart from mean age, hypertension and tumour size/lumpectomy weight. Patients in the OBR group had higher scores for aesthetic outcome and a higher degree of patient satisfaction from the surgical outcome compared to the patients in the BCT‐alone group. Conclusions: The immediate OBR approach in the treatment of centrally located tumours with NAC resection has clear advantages over BCT alone. This approach should be considered for and offered to suitable patients. Abstract : Lumpectomy for centrally located tumors has a high risk for breast deformity. Oncoplastic partial breast reconstruction can be done at the time of lumpectomy. It shows clear advantages, both for patient satisfaction and aesthetic outcome.